Spatial home and road themes in the lyrics of M.I. Tsvetaeva - Y G Pykhtina (RUDN Journal of Studies in Literature and Journalism, 2011)
The article deals with the spatial home and road themes in the lyrics of M.I. Tsvetaeva through the binary oppositions such as home like inherently harmonious, idealized space / home devoid of harmony; material home / spiritual home; a closed, limited home space / open road space.